Is science multicultural? : postcolonialisms, feminisms, and epistemologies - Harding, Sandra G. (Indiana University Press, 1998)
"Sandra Harding explores what practitioners of European/American, feminist, and postcolonial science and technology studies can learn from each other. She discusses the array of postcolonial science studies that have flourished over the last three decades and probes their implications for "northern" science."--Jacket
Keywords: Science -- Social aspects.; Science -- History.; Technology -- History.; Feminism.; Decolonization.; Science -- sociology; Science -- history; Technology -- history; Feminism; Sciences -- Aspect social.; Sciences -- Histoire.; Technologie -- Histoire.; Féminisme.; Décolonisation.; feminism.; SCIENCE -- Philosophy & Social Aspects.; Decolonization; Science; Science -- Social aspects; Technology; Feminismus; Kulturimperialismus; Technik; Wissenschaft; Wissenschaftlich-technischer Fortschritt; Wissenschaftstheorie; Industriestaaten; Entkolonialisierung; Naturwissenschaften; Natuurwetenschappen.; Culturele verschillen.; Cultuur.; Postkolonialisme.; Sekseverschillen.; Épistémologie.; Electronic books.; History